Multifunctional hybrid membranes for photocatalytic and adsorptive removal of water contaminants of emerging concern. (April 2022) - Martins, P.M.; Santos, Bruno; Salazar, H.; Carabineiro, Sónia A.C.; Botelho, G.; Tavares, Carlos J.; Lanceros-Mendez, S.
Abstract: This work focuses on the combination of multifunctional photocatalytic and adsorbent materials in a unique polymeric membrane. For this purpose, Au/TiO2 and Y2 (CO3 )3 nanoparticles were immobilised onto a poly (vinylidene fluoride-hexafluoropropylene), (PVDF-HFP) membrane, and the physical-chemical characterisation of these materials was performed, as well as pollutant removal efficiency. An efficient TiO2 functionalisation with gold nanoparticles was achieved, endowing these particles with the capability to absorb visible radiation absorption. A favourable porous structure was obtained for the membranes, with an average pore size of 4 μm, and the nanoparticles immobilisation did not alter the chemical properties of the polymeric membrane. The produced hybrid materials, including both the Au/TiO2 and Y2 (CO3 )3 nanoparticles, presented an efficiency of 57% in the degradation of norfloxacin (5 mg/L) under ultraviolet radiation for 120 min, 80% under visible radiation for 300 min, and 58% in arsenic adsorption for 240 min. These membranes represent a new multifunctional platform for removing several pollutants, which may allow their incorporation in more efficient and less energy-consuming water treatment processes favouring its application, even in low energy resources countries. Graphical abstract: Image 1 Highlights: Synthesis of Au–TiO2 nanocomposites with ability to absorb visible radiation. Production of porous multifunctional Au–TiO2 /Yttrium/PVDF-HFP membranes. Photocatalytic and adsorptive efficiency tested in norfloxacin and arsenic removal. Multifunctional tests performed for simultaneous photocatalysis and adsorption.